The impact of transformational leadership on employee performance: the mediating role of innovative work behaviour - Morteza Piri; Majid Abdi (Annals of Management and Organization Research, 2025)
Purpose: This study aims to examine and evaluate the impact of transformational leadership on employee performance, with innovative work behavior serving as a mediating variable. The research focuses on industrial organizations in Iran, using a sample of 155 respondents from various sectors. Methodology/Approach: This study employs the Structural Equation Modeling (SEM) technique using the AMOS software. The findings reveal that transformational leadership has a positive and significant impact on employee performance. Results: The results of this study indicate that transformational leadership positively influences employee performance, with innovative work behavior serving as a significant mediator. Transformational leadership also has a strong positive effect on fostering innovative work behavior, which in turn enhances employee performance. Limitations: The limitations of this study include the focus on industrial organizations in Iran, which may limit the generalizability of the findings to other regions or sectors. Additionally, the study relies on self-reported data from employees, which may introduce bias. Conclusion: The dynamics of leadership and employee performance are central to the success and sustainability of organizations, especially in competitive environments such as those found within Iran's industrial sector. Contribution: This study contributes to the existing literature by highlighting the role of transformational leadership in enhancing employee performance through innovative work behavior as a mediating factor. It offers valuable insights into how leadership styles can foster innovation and improve organizational performance, particularly within industrial organizations in Iran.